Spatial Distribution of Housing Investment and Perception of Earthquake Risk in Istanbul Metropolitan Area - Tuba Cekic; Ela Yazici (European Regional Science Association (ERSA), 2011)
Istanbul, the largest metropolitan area in Turkey with a population of over 15 million inhabitants, lies close to major and active fault lines and has been previously hit by fatal earthquakes several times. Facing a high seismic risk as forecasted in a number of studies; Istanbul is particularly vulnerable due to the high density of old housing areas in the city center. Although there is a great body of knowledge in the literature focusing on the seismic risk of Istanbul and possible scenarios to strengthen the capacity for emergency preparedness in the event of future earthquakes, the attitudes and perceptions of housing investors living under the threat of the earthquake is yet to be explored. This study is an attempt to address this gap and aims to investigate the relationship between the location of the housing investment and perception of earthquake risk of the investors. Data was collected by means of a questionnaire from 117 participants, who made an investment in housing in Istanbul since 1999 Kocaeli earthquake. ArcGIS is used to indicate the spatial distribution of investment and the results provide empirical evidence of how spatial distribution of housing investment differs depending on the earthquake risk perception of the investors.
Keywords: 330